Nicotine-induced differential modulation of autoimmune arthritis in the Lewis rat involves changes in IL-17 and anti-cyclic citrullinated peptide antibodies - Yu, Hua (2011)
OBJECTIVE: Rheumatoid arthritis (RA) is a debilitating autoimmune disease. Smoking is an important environmental factor in a subset of RA patients. Furthermore, the role of the cholinergic anti-inflammatory pathway in autoimmune inflammation is increasingly being realized. Nicotine is a major component of cigarette smoke and it also stimulates the α7-nicotinic acetylcholine receptors. Therefore, defining the mechanisms underlying the immunomodulatory effects of nicotine on arthritis is of high relevance. We have addressed this using the rat adjuvant-induced arthritis model of human RA. METHODS: Lewis rats were immunized s.c. with heat-killed M. tuberculosis H37Ra (Mtb) for disease induction. Rats were treated with nicotine i.p. either before (pretreatment) or after (posttreatment) the onset of AA. Control rats received the vehicle (buffer) in place of nicotine. The severity of arthritis was assessed and graded. The draining lymph node cells (LNC) were tested for T cell proliferative and cytokine responses against the disease-related antigen, mycobacterial heat-shock protein 65 (Bhsp65). The sera were tested for anti-cyclic citrullinated peptide antibodies (a-CCP) and anti-Bhsp65 antibodies. RESULTS: Nicotine-pretreatment aggravated arthritis, whereas nicotine posttreatment suppressed the disease. This altered severity of AA directly correlated with the levels of the aCCP antibodies, of the Th1/Th17 cytokines, and of the corresponding dendritic cell-derived cytokines. The majority of these effects on cellular responses could be replicated in vitro. CONCLUSION: Nicotine-induced modulation of AA involves specific alterations in the disease-related cellular and humoral immune responses in AA. These results are of significance in advancing our understanding of the pathogenesis of RA.